Factors Associated with Midterm Visual Field Variability in Patients with Stable Glaucoma. (9th December 2019) - Guimarães, Maria Emília V.; Gracitelli, Carolina P. B.; Dorairaj, Syril; Kanadani, Fábio N.; Prata, Tiago S.
Abstract : Purpose . To evaluate factors associated with midterm visual field (VF) variability in stable glaucoma patients in Brazil. Methods . This retrospective observational study included 59 eyes of 39 stable glaucoma patients. Baseline data assessed were age, gender, educational level, intraocular pressure (IOP), central corneal thickness, best-corrected visual acuity, spherical equivalent, number of hypotensive eye drops, type of glaucoma, number of VFs performed, follow-up in years, lens status, visual field index (VFI) values from the last 5 VF (standard automated perimetry (SAP)) tests, the presence or absence of central scotoma in the VF test, and the level of glaucomatous damage according to the VF mean deviation (MD) index of the last VFs. The 5 latest VFI scores were used to calculate the mean, the standard deviation (SD), and the coefficient of variation (CV). We divided the eyes into 2 groups, being group 1 comprised by the 29 eyes presenting the lowest CV values and group 2 comprised by the 30 eyes presenting the highest CV values. GEE models were used to compare the CV and demographic and clinical parameters of all participants. Results . Mean age of all subjects was 65.8 ± 10.1 years. 54.0% were women. Average SAP MD values for groups 1 and 2 were −2.8 ± 3.1 dB and −6.2 ± 4.1 dB, respectively (P = 0.006 ). Average SAP VFI values for groups 1 and 2 were 95.6 ± 5.9% and 85.9 ± 11.3%, respectively (P = 0.002 ). There was a statistically significant association between CV and SAP MD values (P = 0.006 ). A worse SAP MD and VFI were associated with a higher CV. In addition, even adjusting for potential confounding factors (age and level of education), the association between CV and the SAP MD and between CV and VFI remained significant (P ≤ 0.010 ). Conclusion . Glaucomatous patients with worse VF sensitivity scores (both MD and VFI indices) present higher VF test variability.